Emerging Roles of Exosomes in Huntington's Disease - Ananbeh, Hanadi; Vodicka, Petr; Kupcova Skalnikova, Helena (International journal of molecular sciences, 2021)
Huntington's disease (HD) is a rare hereditary autosomal dominant neurodegenerative disorder, which is caused by expression of mutant huntingtin protein (mHTT) with an abnormal number of glutamine repeats in its N terminus, and characterized by intracellular mHTT aggregates (inclusions) in the brain. Exosomes are small extracellular vesicles that are secreted generally by all cell types and can be isolated from almost all body fluids such as blood, urine, saliva, and cerebrospinal fluid. Exosomes may participate in the spreading of toxic misfolded proteins across the central nervous system in neurodegenerative diseases. In HD, such propagation of mHTT was observed both in vitro and in vivo. On the other hand, exosomes might carry molecules with neuroprotective effects. In addition, due to their capability to cross blood-brain barrier, exosomes hold great potential as sources of biomarkers available from periphery or carriers of therapeutics into the central nervous system. In this review, we discuss the emerging roles of exosomes in HD pathogenesis, diagnosis, and therapy.
Keywords: Animals; Huntingtonova nemoc; biologické modely; therapy; neurodegeneration; lidé; Models, Biological; Huntington’s disease; protein huntingtin; biomarker; sbalování proteinů; Protein Folding; exozómy; Huntington Disease; exosome; huntingtin; Drug Delivery Systems; Huntingtin Protein; polyQ; lékové transportní systémy; zvířata; extracellular vesicle; Exosomes; Humans